2021
DOI: 10.1080/16549716.2021.1936792
|View full text |Cite
|
Sign up to set email alerts
|

High cellphone use associated with greater risk of depression among young women aged 15–24 years in Soweto and Durban, South Africa

Abstract: Background The ubiquity of cellular phone (cellphone) use in young people’s daily lives has emerged as a priority area of concern for youth mental health. Objective This study measured the prevalence of depression and its association with high cellphone use among youth in Soweto and Durban, South Africa. Methods We analysed cross-sectional, baseline survey data among youth aged 16–24 who participated in a dual-site cohort study, ‘AYAZAZI’, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
1
5
0
1
Order By: Relevance
“…According to the current study finding result, respondents who had depression increase 2.45 units on problematic social media use which was similar with the study finding done in United states [ 52 ], Nigeria [ 30 ], South Africa [ 31 ]. The possible reason for this may be that people who are depressed may be more likely to utilize problematic social media platforms like Facebook, Twitter, and YouTube.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the current study finding result, respondents who had depression increase 2.45 units on problematic social media use which was similar with the study finding done in United states [ 52 ], Nigeria [ 30 ], South Africa [ 31 ]. The possible reason for this may be that people who are depressed may be more likely to utilize problematic social media platforms like Facebook, Twitter, and YouTube.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, 43.3% had likely depression and 22.4% of the students in a Zambian study reported having a social media addiction. The most problematic smartphone use risk profile is that of a female, under the age of 21, with low self-esteem who lives away from home, making her more vulnerable to problems and also to depression and anxiety [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…While detailed socio-demographic information (e.g., socio-economic status (SES), education, food-security [ 77 ]), mental health (e.g., stress [ 78 ], depression [ 64 ]), experiences of violence [ 14 ], and substance use were captured during the quantitative AYAZAZI questionnaire, we did not re-ask participants about these factors at the time of the qualitative cognitive interview (3–5 years later), as such we were limited in the ability to compare findings across these factors.…”
Section: Discussion Recommendation and Reflectionsmentioning
confidence: 99%
“…AYAZAZI RIGHTS (Rapid Investigation of Gendered Health outcomes in the Time of Sars-Cov-2) took place over six months between December 2021 and May 2022, recruiting youth aged 16-24 from across eThekwini district South Africa. AYAZAZI stems from prior South African adolescent and youth health research [34][35][36][37], where AYA stands for adolescents and young adults, and "Zazi" meaning knowing themselves in isiZulu. The city of Durban, situated within eThekwini district, has been criticized their conservative views on LGBTQ + acceptance [38] and the lack of political response to the high sustained incidents of LGBTQ + hate crimes occurring within and around the city in recent years [39].…”
Section: Study Settingmentioning
confidence: 99%